The Information Technology Capability and Financial Performance of Global Auto Firms in Thailand: The Role of the Supply Chain as a System of Internal and External Collaboration - Sumalee Srisuponvanit; Jetsalid Anesukanjanakul; Chonticha Somjai; Vanisa Pakvichai (International Journal of Supply Chain Management, 2019)
The researcher specifies the relation between the latent and observed variables and inter-correlation is allowed between all the factors. This research is based on proposing and evaluating the model based on the association between internal and external collaboration, IT capability, and performance of a firm. The study results in important implications, which are important from managerial and theoretical perspectives. The study contributes in a significant way through testing empirically the theoretical assumptions in the previous literature based on the influence of IT on firm performance and collaboration. The study has used the SEM-PLS as a statistical technique to answer the research questions. In this research, it has been considered that there are two constructs of collaboration. Separate constructs have been developed for internal and external collaboration. Moreover, stages are involved in collaboration including simple sharing of information to a truly developed collaboration. A key finding of this study is the influence of internal collaboration on the performance of firm. This finding has been suggested by several research studies, but it does not confirm the crucial role served by internal collaboration. The study, which is among the pioneering studies on the issue will provide policy guidelines to relevant ministry and also helps the researchers in understanding the issues in the Thai auto industry.